A critical review of analytical methods in pretreatment of lignocelluloses: Composition, imaging, and crystallinity. (January 2016) - Karimi, Keikhosro; Taherzadeh, Mohammad J.
Graphical abstract: Highlights: Pretreatment of lignocelluloses are among the crucial steps in a number of bioprocesses. Compositional, imaging, and crystallinity measurements are widely used for analysis. Advantages, drawbacks, approaches, practical details, and points are presented. The methods need special care and preparations, discussed in this paper. Abstract: Lignocelluloses are widely investigated as renewable substrates to produce biofuels, e.g., ethanol, methane, hydrogen, and butanol, as well as chemicals such as citric acid, lactic acid, and xanthan gum. However, lignocelluloses have a recalcitrance structure to resist microbial and enzymatic attacks; therefore, many physical, thermal, chemical, and biological pretreatment methods have been developed to open up their structure. The efficiency of these pretreatments was studied using a variety of analytical methods that address their image, composition, crystallinity, degree of polymerization, enzyme adsorption/desorption, and accessibility. This paper presents a critical review of the first three categories of these methods as well as their constraints in various applications. The advantages, drawbacks, approaches, practical details, and some points that should be considered in the experimental methods to reach reliable and promising conclusions are also discussed.